The Sixteenth Iron in the Nitrogenase MoFe Protein1. Issue 40 (21st August 2013) - Zhang, Limei; Kaiser, Jens T.; Meloni, Gabriele; Yang, Kun‐Yun; Spatzal, Thomas; Andrade, Susana L. A.; Einsle, Oliver; Howard, James B.; Rees, Douglas C.
<x xml:space="preserve">Abstract</x> Another iron in the fire: X‐ray anomalous diffraction studies on the nitrogenase MoFe protein show the presence of a mononuclear iron site, designated as Fe16, which was previously identified as either Ca2+ or Mg2+. The position of the absorption edge indicates that this site is in the oxidation state +2. The high sequence conservation of the residues coordinated to Fe16 emphasizes the potential importance of the site in nitrogenase.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>